Comparing temporal patterns in body condition of ringed seals living within their core geographic range with those living at the edge. Issue 10 (23rd June 2020) - Ferguson, Steven H.; Yurkowski, David J.; Young, Brent G.; Fisk, Aaron T.; Muir, Derek C. G.; Zhu, Xinhua; Thiemann, Gregory W.
Abstract : Ecological theory suggests that demographic responses by populations to environmental change vary depending on whether individuals inhabit central or peripheral regions within the species' geographic range. Here, we tested this prediction by comparing a population of ringed seals Pusa hispida located at high latitudes as part of their core range (core) with a population located at the southern extremity of their range (peripheral). First, we compared the two regions' environmental trends in timing of sea‐ice breakup and freeze‐up, open‐water duration and the North Atlantic Oscillation (NAO). We found that the core region shifted to progressively warmer conditions in the early 1990s; whereas, in the peripheral region, the warming trend shifted in 1999 to one with no warming trend but high inter‐annual variability. Next, we examined how body condition, inferred from blubber depth, responded to temporal changes in sea‐ice and climatic variables – variables that have been shown to influence ringed seal demography. Core seals displayed minimal seasonal changes in body condition; whereas peripheral seals displayed a 20–60% amplitude seasonal change in body condition with a phase shift to earlier initiation of fat accumulation and loss. Finally, we tested for interannual differences and found that both core and peripheral seals responded similarly with decreased body condition following more positive NAO. Environmental variables influenced body condition in opposite directions between the two regions with core seals declining in body condition with later spring breakup and shorter open‐water duration, whereas peripheral seals showed opposite relationships. Seals living at the core likely benefit from an evolved match between adaptation and environmental variation resulting in dampened seasonal and interannual fluctuations in body condition. Knowledge of how different populations respond to environmental change depending on geographic location within a species range can assist in anticipating population specific responses to climate warming.